A non-inferiority trial of Prolonged Exposure for posttraumatic stress disorder: In person versus home-based telehealth. (February 2017) - Acierno, Ron; Knapp, Rebecca; Tuerk, Peter; Gilmore, Amanda K.; Lejuez, Carl; Ruggiero, Kenneth; Muzzy, Wendy; Egede, Leonard; Hernandez-Tejada, Melba A.; Foa, Edna B.
Abstract: This is the first randomized controlled trial to evaluate non-inferiority of Prolonged Exposure (PE) delivered via home-based telehealth (HBT) compared to standard in-person (IP) PE. One-hundred thirty two Veterans recruited from a Southeastern Veterans Affairs Medical Center and affiliated University who met criteria for posttraumatic stress disorder (PTSD) were randomized to receive PE via HBT or PE via IP. Results indicated that PE-HBT was non-inferior to PE-IP in terms of reducing PTSD scores at post-treatment, 3 and 6 month follow-up. However, non-inferiority hypotheses for depression were only supported at 6 month follow-up. HBT has great potential to reduce patient burden associated with receiving treatment in terms of travel time, travel cost, lost work, and stigma without sacrificing efficacy. These findings indicate that telehealth treatment delivered directly into patients' homes may dramatically increase the reach of this evidence-based therapy for PTSD without diminishing effectiveness. Highlights: Prolonged Exposure (PE) decreases posttraumatic stress disorder (PTSD) symptoms. Home-based telehealth (HBT) was compared to in person (IP) delivery of PE. HBT-PE was non-inferior to IP-PE in terms of PTSD symptoms at post, 3 and 6 month followup points. HBT-PE was non-inferior to IP-PE in depression symptoms at 6-month follow-up only. HBT-PE can increase the reach of this evidence-based treatment for PTSD.